Diffusion tensor quantification of the relations between microstructural and macrostructural indices of white matter and reading - Frye, Richard E. (Wiley Subscription Services, Inc., A Wiley Company, 2010)

(untitled) (Hum Brain Mapp)
Few researchers agree about the relationship between fronto–temporo–parietal white matter microstructure and reading skills. Unlike many previous reports, which only measured fractional anisotropy, we have also measured macroscopic volume (regional white matter tract volume) and three microstructural indices (axial, radial, and mean diffusivity) to increase interpretability of our findings. We examined the reading‐related skills and white matter structure in 10 adolescents and adults with a history of poor reading and 20 age‐matched typical readers. We applied a diffusion tensor imaging atlas‐based algorithm to major white matter pathways. The relation of white matter structural indices to reading group, hemisphere, and reading‐related skill was analyzed using linear models. White matter microstructural indices were related to performance on a sublexical decoding task, but the relations between particular microstructural indices and sublexical decoding ability and reading group were different for association (i.e., cortical–cortical) and projection (i.e., subcortical–cortical) white matter pathways. Changes in projection pathways were consistent with alterations in white matter organization and axonal size, whereas changes in association pathways were consistent with alternations in pathway complexity. Changes in macrostructure paralleled changes in microstructure. We conclude that the relations between several microstructural indices and factors related to reading ability are different for association and projection pathways. Hum Brain Mapp, 2011. © 2010 Wiley‐Liss, Inc.